2012
DOI: 10.1007/978-3-642-30541-2_3
|View full text |Cite
|
Sign up to set email alerts
|

Some Typical Properties of the Spatial Preferred Attachment Model

Abstract: Abstract. We investigate a stochastic model for complex networks, based on a spatial embedding of the nodes, called the Spatial Preferred Attachment (SPA) model. In the SPA model, nodes have spheres of influence of varying size, and new nodes may only link to a node if they fall within its influence region. The spatial embedding of the nodes models the background knowledge or identity of the node, which influences its link environment. In this paper, we focus on the (directed) diameter, small separators, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 32 publications
(31 reference statements)
0
41
0
1
Order By: Relevance
“…The SPA model produces scale-free networks, which exhibit many of the characteristics of reallife networks (see [1,19]). In [31], it was shown that the SPA model gave the best fit, in terms of graph structure, for a series of social networks derived from Facebook.…”
Section: Random Graph Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SPA model produces scale-free networks, which exhibit many of the characteristics of reallife networks (see [1,19]). In [31], it was shown that the SPA model gave the best fit, in terms of graph structure, for a series of social networks derived from Facebook.…”
Section: Random Graph Modelsmentioning
confidence: 99%
“…We will use the geometry of the model to obtain a suitable partition that yields high modularity of G n . The following properties (proved many times; see, for example, [1,19]) are the only properties of the model that will be used in the proof: a.a.s. for every pair i, t such that 1 ≤ i ≤ t ≤ n we have that…”
Section: The Spatial Preferential Attachment Modelmentioning
confidence: 99%
“…In the case a = 1/2, the profile function ϕ only takes the values zero and one, thus the decision is not random and we connect two vertices whenever they are close enough. The degree-based preferential attachment model in discrete time for this choice of ϕ was introduced in [1] and further studied in [5] and [16]. This particular choice for the profile function helps to get a better understanding of the problems and properties of this model, see for example Section 5.…”
Section: The Age-based Spatial Preferential Attachment Networkmentioning
confidence: 99%
“…The geometric nature of the network implies that there is a high amount of local clustering [10]. In [3], logarithmic bounds on the directed diameter were given. In [9] it was shown that the effective undirected diameter is also logarithmically bounded.…”
Section: The Spa Modelmentioning
confidence: 99%